Representasi Warna Ungu dalam Novel The Color Purple Karya Alice Walker: Analisis Semiotika - Nessa Aqila Anggraini (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2022)
This article aims to represent the color purple in Alice Walker's novel The Color Purple. This article uses the semiotic study of Charles Sanders Pierce. The process of meaning according to Pierce is divided into three stages, namely the absorption of the signifier (representament), the appointment of the representamen on the object and the interpretation of the further (interpretant). This paper also uses a qualitative descriptive approach. The results of the research in this paper indicate that the researcher found a signifier (representament) of the word